ANALISIS KARIOTIPE ULAR TRAWANG (COELOGNATHUS RADIATUS, (BOIE 1827)) - Qurniawan, Tony Febri; Arisuryanti, Tuty; Nur Handayani, Niken Satuti (JURNAL BIOLOGI INDONESIA, 2012)
Analysis of Radiated Ratsnakes (Coelognathus radiatus, (Boie 1827) Karyotype. Radiatedratsnake is a reptile which has an economic potential an export comodyty. However, there arefew reports on genetic studies of radiated ratsnake. The aim of this research was to examinechromosome characters of the radiated ratsnake collected from Sewon, Bantul, Daerah IstimewaYogyakarta. Chromosome preparation method used was splash using blood culture. The resultsrevealed that the diploid chromosome number (2n) of radiated ratsnake was 30, classified asmetacentric (chromosome pairs number 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, dan 11), submetacentric(chromosome pairs number 12 and 13), and telocentric (chromosome pairs number 14 and 15).Therefore the karyotype formula of radiated ratsnake was 2n = 2x = 30 = 22 m + 4 sm + 4 t. Theresult showed that the shortest of short arm chromosomes was 0 ?m, the longest one was0.665 ± 0.0504 ?m, the shortest of long arm chromosomes was 0.268 ± 0.0011?m, the longestone was 0.746 ± 0.0059 ?m, the shortest of total length chromosomes was 0.27 ± 0.001 ?m, andthe longest of total length chromosomes was 1.41 ± 0.045 ?m. The R value was 5.267 ± 0.15408indicating that radiated ratsnake from Sewon, Bantul, Daerah Istimewa Yogyakarta haschromosome variation size.Keywords: Coelognathus radiatus, blood culture, chromosome character, karyotype